Fertility, Drought, Migration, and Risk - Oded Stark (Essays on Population Economics - in Memory of Alfred Sauvy, 1991)
If children confer new insurance benefits or are more reliable suppliers of old insurance benefits, demand for offspring may rise. Although it might be costly to prepare children to provide enhanced benefits, the costs might be even higher when the family has only a small number of children. Hence the possibility exists that the demand for children and consequently the level of fertility will rise. If, in environments characterized by spatially covariant risks, such as rural India, the insurance benefits are provided by daughters who marry into distant households, more daughters (and more children) - not less - would be required to create a spatially diversified, income-pooling family that can mitigate the hazards of agricultural production and reduce income variability.
Keywords: 330